White paper on the second and final report of the wages and salaries review commission, 1970-71 - Nigeria. National Salaries, Incomes, and Wages Commission (Lagos : Federal Ministry of Information, 1971)
This is the final report on the salaries and wages review at all levels in the Public services, and in the Statutory Public Corporations and State-owned companies, 1970-71.
ne 16/04/2019
Ref
Keywords: Wages--Government policy; Civil service--Salaries, etc; Nigeria